Find where the function f(x)=3x^4-4x^3-12x^2+5 is increasing and decreasing?

3 Answers | Add Yours

hala718's profile pic

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on


First we need to find the critical points in which the function changes behavior (increasing or decreasing)

To determine the critical points, we need to find f'(x)

f'(x)=12x^3-12x^2-24x = 12x(x^2-x-2)=12x(x-2)(x+1)

The critical points are 0, 2, -1

Then we have 4 intervals where the function change behavior

(-inf,-1), (-1,0), (0,2), (2,inf)

1. when x<-1 ==> f'(x) >0 ==> f is decreasing

2. when -1<x<0 ==> f'(x) <0 ==> f is increasing

2. when 0<x<2 ==> f'(x) < 0 ==> f is decreasing

4. when x>2 ==> f'(x)>0 ==> f is increasing

Top Answer

giorgiana1976's profile pic

giorgiana1976 | College Teacher | (Level 3) Valedictorian

Posted on

For this reason, we'll use the Increasing/Decreasing Test.

Of course, to use this test, we have to differentiate the function first:


We know that the derivative of the sum is the sum of derivatives:


We'll factorize:


We'll factorize again, writing the expression



Now, we'll find the critical points:








And now, we'll begin to analyze the behaviour of the derivative, around these critical points:

For x<-1:




Multiplying 12x(x-2)(x+1)=(-)*(-)*(-)<0

f'(x)<0, so f is decreasing over (-inf, -1).

For -1<x<0:




Multiplying 12x(x-2)(x+1)=(-)*(-)*(+)>0

f'(x)>0, so f is increasing over (-1, 0).

For 0<x<2:




Multiplying 12x(x-2)(x+1)=(+)*(-)*(+)<0

f'(x)<0, so f is decreasing over (0, 2).

For x>2:






Multiplying 12x(x-2)(x+1)=(+)*(+)*(+)>0

f'(x)>0, so f is increasing over (2, inf).

neela's profile pic

neela | High School Teacher | (Level 3) Valedictorian

Posted on

f(x) = 3x^4-4x^3-12x^2+5

 To determine the point where f(x) is increasing and then decresing.


The point wher f(x) increases on left and decrease on the right is the point where f(x) attains maximum . So  we  can   f'(c) = 0  for c and see which value of c makes f" (c) negative.

f'(x) = 0 gives: (3x^4-4x^3-12x^2+5)' = 0. Or

12x^3-12x^2-24x = 0. Or dividing by 12  we get:

x(x^2-x-2) = 0. Or

x(x-2)(x+1) = 0. Or

x=0, x =2 or x = -1

f"(x) = (12x^3-12x^2-24x)' =  36x-24x-24 = 12(3x^2-2x-2)

f(0) = 12*(-2) is - ve.

f(2) = 12(3*2^2-2*2-2) = 12*(6) is positive.

f(-1) = 12(3*(-1)^2-2(-1)-2) = 12*3 is positive.

Therefore f(0) maximum at x= 0 0, where f(x) is incresing on the left of x= 0 and f(x) decreases on the right of x= 0.

We’ve answered 317,824 questions. We can answer yours, too.

Ask a question